Systematic review of the influence of socioeconomic deprivation on mortality after colorectal surgery. Issue 8 (16th April 2018) - Poulton, T E; Salih, T; Martin, P; Rojas-Garcia, A; Raine, R; Moonesinghe, S R
Abstract: Background: Socioeconomic deprivation is a potentially important factor influencing surgical outcomes. This systematic review aimed to summarize the evidence for any association between socioeconomic group and mortality after colorectal surgery, and to report the definitions of deprivation used and the approaches taken to adjust for co-morbidity in this patient population. Methods: MEDLINE, Embase, the Cochrane Library and Web of Science were searched for studies up to November 2016 on adult patients undergoing major colorectal surgery, which reported on mortality according to socioeconomic group. Risk of bias and study quality were assessed by extracting data relating to study size, and variations in inclusion and exclusion criteria. Quality was assessed using a modification of a previously described assessment tool. Results: The literature search identified 59 studies published between 1993 and 2016, reporting on 2 698 403 patients from eight countries. Overall findings showed evidence for higher mortality in more deprived socioeconomic groups, both in the perioperative period and in the longer term. Studies differed in how they defined socioeconomic groups, but the most common approach was to use one of a selection of multifactorial indices based on small geographical areas. There was no consistent approach to adjusting for co-morbidity but, where this was considered, the Charlson Co-morbidity Index was most frequently used. Conclusion: This systematic review suggests that socioeconomic deprivation influences mortality after colorectal surgery. Abstract : Major differences in mortality